The effect of Myrtus communis L. ethanol extract on the small intestine and lungs in experimental thermal burn injury. (October 2020) - Ozcan, Ozan; Ipekci, Hazal; Alev, Burcin; Ustundag, Unsal Veli; Sen, Ali; Emekli-Alturfan, Ebru; Sener, Goksel; Yarat, Aysen; Tunali-Akbay, Tugba
Abstract: Thermal trauma can damage organs away from the skin burn site and lead to multiple organ dysfunction. Following thermal injury, all tissues are exposed to ischemia, and as a result, resuscitation and reperfusion occur during the burning shock. Burn damage starts systemic inflammatory reactions that produce toxins and reactive oxygen radicals that lead to peroxidation. This study aimed to investigate, for the first time, the possible antioxidant effects of Myrtus communis ethanol extract on burn-induced oxidative distant organ injury orally. The thermal trauma was generated under ether anesthesia by exposing the dorsum of rats to 90  ° C water bath for 10 s. 100 mg/kg/day Mrytus communis ethanol extract was applied orally for two days. Malondialdehyde (MDA) and glutathione (GSH) levels, glutatinone-S-transferase (GST), superoxidedismutase (SOD) and catalase (CAT) activities were determined to detect the possible antioxidant effects of myrtle on small intestine and lung tissues. Burn damage significantly increased MDA levels in lung and small intestine tissues, and significantly decreased GSH levels, CAT and GST activities in the small intestine and lung tissues compared to control group. Mrytus communis ethanol extract decreased MDA level and increased GSH level, SOD, CAT and GST activities significantly in either small intestine or lung tissues. Mrytus communis extract may be an ideal candidate to be used as an antioxidant adjunct to improve oxidative distant organ damage to limit the systemic inflammatory response and decreasing the recovery time after thermal injury. Graphical abstract: Image 1 Highlights: The first study on the healing effects of Myrtus communis against burn-induced distant organ damage. Myrtus communis showed beneficial effects on the small intestine and lungs in thermal burn injury. Myrtus communis exhibited significant antioxidant effect. It may be a promising agent in the treatment of burn-induced oxidative distant organ damage.